Analysis of Competence Motivation and Employee Character on Public Service Quality Through Human Resources Readiness at the Ministry of Law and Human Rights North Sumatra Regional Office - Windy Puspita Langkana; Prihatin Lumbanraja; Hamdani Harahap (LOCUS MEDIA PUBLISHING, 2022)
The provision of public services is one of the most essential government duties since it ensures a nation's progress and promotes wealth and fairness in society. This research is a quantitative research conducted at the Regional Office of the Ministry of Law and Human Rights of North Sumatra Province, this study examines the effect of competence, motivation, and character of employees on Public Service Quality and HR readiness as intervening variables. The number of respondents in this study were 67 people from a total population of 203 people. From the findings, the direct effect shows that: (1) competence and employee character have a positive and significant effect on HR readiness, but the motivational variable has no effect on HR readiness. While the variables of motivation and character of employees have a significant effect on Public Service Quality, while the variables of competence and readiness of human resources have no direct effect on Public Service Quality. (2) Testing the competence, motivation, and character of workers has an indirect effect on Public Service Quality.